LITERATURE REVIEW: ANALYSIS OF FACTORS AFFECTING PREMENSTRUAL SYNDROME IN GIRLS ADOLESCENT - Dorkas Day Mbati; Laily Hidayati; Ni Ketut Alit Armini (Universitas Airlangga, 2021)
Introduction: Premenstrual syndrome in adolescent girls is very disturbing daily activities. Changes such as feeling sensitive or irritable, lack of confidence, difficulty concentrating, crying easily, restlessness and anxiety. Premenstrual syndrome in adolescents causes anxiety so that it can result in decreased interest in activities. The purpose of this study is to explain the factors that influence premenstrual syndrome in adolescent girls based on empirical studies in the last five years.Method: The literature review article search was conducted in five databases (Scopus, Proquest, Pubmed, Science Direct and Google Scholar), the search was conducted from July to August 2020. A prism checklist was used to guide this review. Analyzed and tabulated data on articles. Title, abstract, full text and methodology were assessed to determine the feasibility of the study.Result: There were 10 studies that matched the research inclusion criteria, the studies were divided into two themes, namely the influencing factors of premenstrual syndrome (n= 8) and the impact of premenstrual syndrome (n= 2).Conclusion: Factors that affect premenstrual syndrome include: physiological factors include (age, education, length of menstruation, menstrual cycle, menstrual history, physical activity), nutritional factors include (diet, coffee consumption), psychological factors include (stress, feeling uncomfortable). , feelings of insecurity) and the external factor is the use of the internet. Premenstrual syndrome can physically show in the form of headache, breast tenderness, swelling of the extremities, abdominal and heartburn pain and psychologically shows anxiety, withdrawal, confusion, depression and irritability.